Temperature induced changes in the heterocyst glycolipid composition of N2 fixing heterocystous cyanobacteria - Bauersachs, T.; Stal, L.; Grego, M.; Schwark, Lorenz (Pergamon, 2014)
We investigated the effect of temperature on the heterocyst glycolipid (HG) composition of the diazotrophic heterocystous cyanobacteria Anabaena sp. strain CCY9613 and Nostoc sp. strain CCY9926 grown at 9, 12, 16, 20 and 24 °C. Both strains contained an overall similar composition of heterocyst glycolipids, with 1-(O-hexose)-3,25-hexacosanediols (HG26 diols) and 1-(O-hexose)-3-keto-25-hexacosanols (HG26 keto-ols) dominating minor quantities of 1-(O-hexose)-3,27-octacosanediols (HG28 diols) and 1-(O-hexose)-3-keto-27-octacosanols (HG28 keto-ols). The relative proportion of HG diols vs. HG keto-ols increased with increasing growth temperature, which was quantitatively expressed as HGI26 (heterocyst glycolipid index of 26 carbons). Values of the index decreased from 0.30 to 0.12 in Nostoc CCY9926 and from 0.18 to 0.10 in Anabaena CCY9613 over the temperature interval investigated. Likewise, HGI28 (heterocyst glycolipid index of 28 carbons) values decreased from 0.33 to 0.10 in Nostoc CC9926 and from 0.12 to 0.07 in Anabaena CCY9613 with increasing temperature. Our results thus provide the first evidence that changes in the composition of the heterocyst cell envelope as a function of temperature occur systematically in different heterocystous cyanobacteria and may constitute a mechanism for allowing optimum N2 fixation by regulating the rate of gas diffusion into the heterocyst.